THE SCIENTIFIC PRODUCTION ON BORN GLOBALS IN BRAZILIAN JOURNALS - Sousa, Thiago Alberto Viana de (2020)
Objective: The objective of this article was to analyze the scientific production in brazilian journals in born globals.Method: A bibliometric analysis of the entire scientific production in Brazil up to October 2019 was carried out in journals ranked with Qualis A1 to B3 and papers published in the ANPAD Conference (ENANPAD)Main results: On this field of research, there is a predominance of articles discussing the internationalization process of born globals and the evolution of the concept of internationalization. The largest amount of papers published on the theme are from institutions from the south and southeast of Brazil.Relevance/originality: An analysis of the brazilian scientific production on born globals is useful for researchers in their future studies about internationalization.Theoretical/methodological contributions: This paper contributes to the theoretical evolution of the theme, presenting the development of the research in born globals in Brazil over the years.